Effect of thermophoresis on particle deposition on an inclined plate in variable viscosity fluid flow within a porous medium - J.S. Huang; H.H. Hsu (Case Studies in Thermal Engineering)
Aerosol particles experience thermal thrust due to temperature gradient, moving from high-temperature regions to low-temperature ones, known as thermophoresis. When a temperature difference exists between the fluid and the object's surface, the thermophoretic effect generates a force that directs particles toward a colder wall or pushes them outward from a heated wall. The study of fluid flow through porous media traces its origins to Darcy's law, proposed by the scholar Darcy following experiments in 1856. This law establishes a proportional relationship between the average flow velocity and the hydraulic gradient while inversely relating it to viscosity. This study utilizes the similarity transformation technique, Runge-Kutta integration, and a shooting approach to address the governing equations for continuity, momentum, energy, and concentration fields. The principal aim of this investigation is to analyze the behavior of aerosol particles within a Darcy porous medium subjected to fluid flow of variable viscosity, considering the effects of thermophoresis, magnetic fields, Joule heating, convection, Brownian diffusion, thermal radiation, and internal heat sources. The specific aims include characterizing aerosol particles' concentration distribution as they pass along an inclined plate and calculating particle deposition velocities under hot and cold wall conditions.